2018
DOI: 10.1016/j.bbmt.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Nilotinib for Cytomegalovirus Infection Prophylaxis after Allogeneic Hematopoietic Stem Cell Transplantation: A Single-Arm, Phase II Trial

Abstract: Platelet-derived growth factor receptor-alpha (PDGFRa) is a critical receptor for cytomegalovirus (CMV) entry into cells, leading to subsequent infection. This trial tested whether PDGFRa inhibition by nilotinib could prevent CMV infection in patients after allogeneic stem cell transplantation (allo-HSCT). Nilotinib (200 mg/day) was given continuously after engraftment, and plasma CMV DNA levels were monitored weekly. The primary endpoint was successful prophylaxis of CMV infection, defined as plasma CMV DNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…PDGFR-ɑ has been reported as a critical receptor required for CMV infection [30]. Interestingly, a recent phase 2 study showed that nilotinib could prevent CMV infection after allo-HSCT by inhibiting PDGFRɑ [31]. However, this study was a single-arm study with a small sample size.…”
Section: Discussionmentioning
confidence: 90%
“…PDGFR-ɑ has been reported as a critical receptor required for CMV infection [30]. Interestingly, a recent phase 2 study showed that nilotinib could prevent CMV infection after allo-HSCT by inhibiting PDGFRɑ [31]. However, this study was a single-arm study with a small sample size.…”
Section: Discussionmentioning
confidence: 90%
“…An unusual new approach to HCMV therapy is based on the observation that the gH/gL/gO trimer uses the PDGF (platelet-derived growth factor) receptor for cell entry [46]. In a single arm Phase 2 trial, a receptor kinase inhibitor (nilotinib, an approved drug for treatment of chronic myeloid leukemia), suppressed HCMV infection in 80.6% of HSCT patients ( N = 37) [47].…”
Section: Therapeutic Approachesmentioning
confidence: 99%